2014
DOI: 10.5603/fm.2014.0054
|View full text |Cite
|
Sign up to set email alerts
|

A combined variation of the musculocutaneous nerve associated with a supernumerary head of the biceps brachii muscle

Abstract: Single anatomical variation in the upper limb is common (Folia Morphol 2014; 73, 3: 366-369)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Embryologically, the third head of the BB was considered as a part of the brachialis muscle that was separated by the musculocutaneous nerve, being classified by Kosugi et al (1992); a similar case was also reported by our laboratory (Lee et al 2014). Phylogenetically, variations of the BB were explained as a remnant of a ''tuberculo-septale'' head that, together with short and long heads, is present in hylobates but is a product of regression in humans and anthropoids (de Burlet and Correljé 1919).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Embryologically, the third head of the BB was considered as a part of the brachialis muscle that was separated by the musculocutaneous nerve, being classified by Kosugi et al (1992); a similar case was also reported by our laboratory (Lee et al 2014). Phylogenetically, variations of the BB were explained as a remnant of a ''tuberculo-septale'' head that, together with short and long heads, is present in hylobates but is a product of regression in humans and anthropoids (de Burlet and Correljé 1919).…”
Section: Discussionmentioning
confidence: 64%
“…The prevalence of three supernumerary heads is about 0.17 % (Adachi 1910), in which the extra heads commonly originate from the humerus. The similar fiveheaded BB was recently reported, 100 years thereafter (Lee et al 2014), although a BB with seven heads was once reported without morphological details (Pires de Lima 1923).…”
Section: Introductionmentioning
confidence: 67%
“…Single anatomical variation in the upper limb is common [1]. The brachial plexus is the most variable part of the peripheral nervous system [2].…”
Section: Introductionmentioning
confidence: 99%